Kompensasi Bonus dan Manajemen Laba Riil: Peran Moderasi Komite Audit - Gustina Dwi Lestiani; Wahyu Widarjo (Jurnal Kajian Akuntansi, 2021)
AbstractThis study analyzes the effect of bonus compensation on real earnings management, as well as the effect of the audit committee on the relationship between bonus compensation and real earnings management in manufacturing companies in Indonesia. The sample of this research is manufacturing companies which listed on the Indonesia Stock Exchange in 2016 - 2018. The research sample was selected by purposive sampling method. Hypothesis testing is performed using panel data regression methods and Moderated Regression Analysis (MRA). The research results show that bonus compensation has a positive and significant effect on real earnings management, while the effectiveness of the audit committee does not weaken the effect of bonus compensation on real earnings management. The findings of this study provide an overview to company stakeholders that bonus compensation is one of the factors which motivating company management to practice earnings management, particularly earnings management related to the company's real activities. In addition, this study also provides an overview of the effectiveness of the implementation of corporate governance mechanisms in sample companies, particularly the ineffective supervisory function related to earnings management practices carried out by the audit committee.Keywords: Bonus compensation; Real earnings management; Effectiveness of the audit committee.Abstrak Penelitian ini menganalisis pengaruh kompensasi bonus terhadap manajemen laba riil, serta pengaruh komite audit terhadap hubungan kompensasi bonus dan manajemen laba riil pada perusahaan manufaktur di Indonesia. Sampel penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2016-2018. Sampel penelitian dipilih dengan metode purposive sampling. Pengujian hipotesis dilakukan dengan metode regresi data panel dan Moderated Regression Analysis (MRA). Hasil penelitian menunjukkan kompensasi bonus berpengaruh positif dan signifikan terhadap manajemen laba riil, sedangkan efektivitas komite audit tidak memperlemah pengaruh kompensasi bonus terhadap manajemen laba riil. Temuan penelitian ini memberikan gambaran kepada stakeholder perusahaan bahwa kompensasi bonus merupakan salah satu faktor yang motivasi manajemen perusahaan untuk melakukan praktik manajemen laba, khususnya manajemen laba yang berkaitan dengan aktivitas riil perusahaan. Selain itu, penelitian ini juga memberikan gambaran tentang efektivitas implementasi mekanisme corporate governance pada perusahaan sampel, khususnya belum efektifnya fungsi pengawasan terkait praktik manajemen laba yang dilakukan oleh komite audit.Kata Kunci: Kompensasi bonus; Manajemen laba riil; Efektivitas komite audit